The Prospects for Sustained Growth in Africa : Benchmarking the Constraints - Subramanian, Arvind; Johnson, Simon; Ostry, Jonathan (Washington, D.C. : International Monetary Fund, 2007)
A dozen countries had weak institutions in 1960 and yet sustained high rates of growth subsequently. We use data on their characteristics early in the growth process to create benchmarks with which to evaluate potential constraints on sustained growth for sub-Saharan Africa. This analysis suggests that what are usually regarded as first-order problems-broad institutions, macroeconomic stability, trade openness, education, and inequality-may not now be binding constraints in Africa, although the extent of ill-health, internal conflict, and societal fractionalization do stand out as problems in contemporary Africa. A key question is to what extent Africa can rely on manufactured exports as a mode of "escape from underdevelopment," a strategy successfully deployed by almost all the benchmark countries. The benchmarking comparison specifically raises two key concerns as far as a development strategy based on expanding exports of manufactures is concerned: micro-level institutions that affect the costs of exporting, and the level of the real exchange rate-especially the need to avoid overvaluation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet